Production Simulation Hydrogen Gas from Heavy Fuel Oil Gasification and Life Cycle Assessment (LCA) using UNISIM Design R460.1 and GABI TS Software - Rinaldi Medali Rachman; Dionisius Fransisco Rupang Pangkung (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
Heavy fuel oil utilization via combustion leads to negative impacts towards the environment. A cleaner way of heavy fuel oil utilization should be implemented, gasification is one. Gasification process can convert heavy fuel oil feed into valuable gas like hydrogen. Based on the simulation result, hydrogen purity (on dry basis) was obtained at 98,02% (volume). Study on temperature and addition of gasifying agent was also done. At high gasification temperature, more hydrogen tends to be produced. Steam addition also gives positive effect on hydrogen yield. Environmental impacts evaluation using life cycle assessment method has been performed. Based on the simulation, this process significantly contributes to climate change with the score of 2.630 kgCO2eq. Carbon dioxide utilization via enhanced oil recovery can overcome this problem. From economical point of view, annual net income after tax is at Rp 45.956.031.943,16 with the annual return on investment rate of 59,46%, which is economically justified.